Inverse evolution of helicity from the molecular to the macroscopic level based on N-terminal aromatic amino acids - Liang, Juncong (2022)
Precise control of the emergence of macroscopic helicity with specific handedness is promising in rationally designing chiral nanomaterials, but it is rather challenging. Herein, we present a protocol to address the transmission of helicity at a molecularly resolved level to a macroscopically resolved level, in which process supramolecular chirality undergoes an inversion. A series of N-terminal aromatic amino acids could self-assemble in water, enabling the occurrence of helicity at the molecularly resolved scale, evidenced by the single crystal structure and chiroptical responses. While it failed to transmit the helicity to the macroscopic scale for individual self-assembly, the coassembly with small organic binder through hydrogen bonding interactions allows for the emergence of helical structures at the nano/micrometer scale. Experimental and theoretical results demonstrate that the introduction of extra hydrogen bonds enables a moderate crystallinity of coassemblies with remaining one-dimensional orientation to enhance the helical growth. The transmission of helicity to higher levels by coassembly is accompanied by the helicity inversion, resulting from the exchange of hydrogen bonds. This study presents a rational protocol to precisely control the emergence of macroscopic helicity from molecularly resolved helicity with finely tailored handedness, providing a deeper understanding of the chirality origin in the assembled systems in order to facilitate the design and construction of functional chiral nanomaterials.